2019
DOI: 10.35940/ijrte.c1213.1083s219
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Communication on Employee Performance

Abstract: This study aims to examine types of communication such as horizontal communication, downward communication and upward communication that impact employee performance in a property development company in Malaysia. Survey questionnaire approach was applied to collect data in this study. A total of 120 respondents participated in this research. The results indicated that downward communication (DC) and horizontal communication (HC) have significant positive impacts towards employee performance. The research findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 13 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…So it can be concluded that the organizational communication variable (X1) with elements of ease of obtaining information (X2.1), communication intensity (X2.2), communication effectiveness (X2.3), level of message understanding (X2.4), and attitude change (X2.5). The results of this study support research that had been carried out by Hee et al (2019) which stated that there is a significant effect of communication on employee performance.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…So it can be concluded that the organizational communication variable (X1) with elements of ease of obtaining information (X2.1), communication intensity (X2.2), communication effectiveness (X2.3), level of message understanding (X2.4), and attitude change (X2.5). The results of this study support research that had been carried out by Hee et al (2019) which stated that there is a significant effect of communication on employee performance.…”
Section: Resultssupporting
confidence: 87%
“…Research results from Hakim and Kusdiyanto (2010) showed that there is a significant influence of organizational culture on performance. Research results from Hee et al, (2019) stated that there was a significant effect of communication on employee performance. Research result Arifin et al (2019) stated that job satisfaction has a significant effect on employee performance.…”
Section: Definition Of Communication According Tomentioning
confidence: 99%
“…Gaining employee's commitment to their organization's goals is believed to unlock their potential and achieve heightened levels of performance. Opposite results can lead employees to dissatisfaction or tend to lose interest in their work, higher levels of burnout and stress, absenteeism, intention to quit, and consequently suboptimal healthcare delivery and poor clinical outcomes [54]. Managers of health services organizations in cooperation with the Ministry of Health (MoH) must elicit cooperation and performance of the employees to ensure the quality of care and the morbidities and mortalities may be improved undoubtedly.…”
Section: Discussionmentioning
confidence: 99%
“…Another side, we used a question that was adapted from Li et al l (2021) and Redy et al ( 2019) for a variable work commitment. Meanwhile, for Employee performance, we adapt a questionnaire from Hee et al (2019) and Ramli (2019). The questionnaire in this study contained 22 items which were filled out and returned by all 100 respondents.…”
Section: Methodsmentioning
confidence: 99%